PEMBATALAN PERKAWINAN OLEH PIHAK KETIGA KARENA ADANYA PEMALSUAN IDENTITAS (STUDI PUTUSAN PENGADILAN AGAMA NO.678.PDT.G/2015/PA.MDN) - MAIHENDRA PUJI HASTUTI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. H. M. Hasballah Thaib2. Utary Maharany Barus3. Yefrizawati A legitimate marriage should meet the basic principle and requirements of marriage. If they are fulfilled, the marriage will be revoked, including a marriage which is based on the forgery of identity by one of the new married couple. The research used juridical normative. It also used descriptive analytic method. The result of the research shows that revocation of a marriage is embodied in Article 27 of Law No. 1/1974 in conjunction with Article 72, paragraph 2 of KHI in which the authority to revoke a marriage when there is forgery in identity done by one of the new married couple so that one of them has the right to lodge the revocation of the marriage. Secondly, PPN as the third party in the revocation of the marriage does not have any legal position because PPN has no right to revoke the marriage based on Article 23 of Law No. 1/1974 on Marriage in conjunction with Article 72 of KHI. Thirdly, the judge, in his decision, rejects the lawsuit for the revocation of the marriage due to the forgery of identity by PPN based on Article 23 of Law No. 1/1074 on Marriage in conjunction with Article 72 of KHI.Keywords: Revocation of Marriage, Third Party, Forgery of Identity